Pengaruh Harga dan Promosi Terhadap Minat Beli Konsumen Pada Produk Mie Sedaap di Kos Putri Griya Ardinie Depok - Kalista Mariana Enot; Niken Herawati (WORKFORCE JOURNAL: Manajemen & Bisnis, 2026)
This study aims to determine the effect of price and promotion on consumer purchasing interest in Mie Sedaap products at Kos Putri Griya Ardinie Depok. The sample used in this study was 80 respondents, taken using a purposive sampling method and to determine the size or number of samples used the Slovin formula. Data collection techniques through observation, documentation studies, and questionnaires in the form of primary data, namely distributing questionnaires using Google Form. Data analysis used data quality tests, classical assumption tests, regression coefficient tests, and hypothesis tests. The results of this study are that prices partially have a positive and significant effect on consumer purchasing interest with a t-count value of 5.167 and a significance of 0.000. Promotions partially have a positive and significant effect on consumer purchasing interest with a t-count value of 8.873 and a significance of 0.000. The results of the f test obtained a significance value of 0.000 less than 0.05 and an f-count value of 158.418 greater than the f-table of 3.12, which means that together prices and promotions have a positive and significant effect on consumer purchasing interest.